Enhancement of biogas production in anaerobic co-digestion of subcritical water pre-treated with pineapple waste and cow dung - Aili Hamzah, Adila Fazliyana (2022)
The co-digestion of lignocellulosic waste with manure has been seen to improve the C/N ratio required by the systems to produce higher methane yield compared to mono digestion. Despite the success of co-digestion systems, the complex structure of pineapple waste slows down the digestion process. Subcritical Water (SCW) pre-treatment was introduced to improve the digestibility of pineapple waste. This study aims to evaluate suitable organic loading and mixing ratio of pineapple waste and cow dung for co-digestion process. Then, the SCW pre-treatment conditions of pineapple waste such as temperature, time and water to solid ratio were optimized using Response Surface Methodology (RSM). The impact of untreated and pre-treated pineapple waste on the physicochemical and morphology properties, methane production, its kinetic, and performance in an up-scaled anaerobic digester were further assessed at optimal conditions. Based on volatile solid (VS) contents, five different cow dung to pineapple waste ratios were assessed. The highest biogas and methane yield were obtained at ratio 1:3 with 179.08 mL/g VS and 142.89 mL CH4/g VS. The co-digestion improved the C/N ratio, total ammonia nitrogen (TAN), VS removal, and pH. The kinetic study using the modified Gompertz model showed that the co-digestion process had shortened the lag phase, and the highest biogas production rate was observed at 12.80 mL/g VS. day. For optimization process, the model fitting showed the coefficient of determination (R2) value of 0.9825. The RSM model predicted a maximum biogas yield of 144.17 mL/g VS for pre-treatment conditions at the water to solid ratio of 7.5:1, the temperature at 160°C and the reaction time of 15 minutes. The optimal condition of SCW pre-treatment was at 128.51°C, water to solid ratio of 5.67:1, and reaction time of 5 minutes. The compositional analysis found that the pre-treated pineapple waste reduced lignin, hemicellulose, and cellulose contents. Pre-treated samples yielded 102.42 mL/g VS, which was 23% higher than untreated. Analysis using Fourier Transform Infrared Spectroscopy (FTIR) and Thermogravimetric Analysis (TGA) verified the presence of cellulosic material in the pre-treated pineapple waste. X-ray Diffraction (XRD) analysis indicated changes in the crystallinity index. Scanning Electron Microscopy (SEM) confirmed structural modification of pre-treated pineapple waste and made it accessible for microbial attack. A higher methane yield of 85.05 mL CH4/g VS was observed in pre-treated pineapple waste with a 44% increment. The co-digestion of optimized SCW pre-treated pineapple waste and cow dung was upscaled using 6.4 L lab-scale anaerobic digester. The cumulative biogas produced was 2100 mL which yielded 17.13 mL/g VS. The methane volume was 440 mL with a 36 to 86% methane content. The kinetic study of upscale anaerobic digester showed that the lag phase had shortened, and the highest biogas production rate was observed at 17.53 mL/g VS. day. This suggests that the co-digestion process using SCW pre-treated sample could increase methane production, enhance process efficiency and significantly reduce the digestion time. The co-digestion of SCW pre-treated pineapple waste with cow dung improves biogas production and produces a higher methane yield in comparison to untreated samples. Enhancing biogas production from SCW pre-treated pineapple waste with cow dung appears to be a promising approach for bioenergy recovery.